2019
DOI: 10.1371/journal.pone.0219126
|View full text |Cite
|
Sign up to set email alerts
|

A feature agnostic approach for glaucoma detection in OCT volumes

Abstract: Optical coherence tomography (OCT) based measurements of retinal layer thickness, such as the retinal nerve fibre layer (RNFL) and the ganglion cell with inner plexiform layer (GCIPL) are commonly employed for the diagnosis and monitoring of glaucoma. Previously, machine learning techniques have relied on segmentation-based imaging features such as the peripapillary RNFL thickness and the cup-to-disc ratio. Here, we propose a deep learning technique that classifies eyes as healthy or glaucomatous directly from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 27 publications
5
128
0
3
Order By: Relevance
“…The ability of DL models to use visual cues that are not apparent to the human eye has been previously demonstrated in another study in which retinal angiograms were generated from OCT images [39]. This finding is also consistent with a recent study that used unsegmented OCT scans and reported the involvement of outer retinal layers in a DL model that detects glaucoma [43,77].…”
Section: Discussionsupporting
confidence: 87%
“…The ability of DL models to use visual cues that are not apparent to the human eye has been previously demonstrated in another study in which retinal angiograms were generated from OCT images [39]. This finding is also consistent with a recent study that used unsegmented OCT scans and reported the involvement of outer retinal layers in a DL model that detects glaucoma [43,77].…”
Section: Discussionsupporting
confidence: 87%
“…With surrogate label assignment for VF measurement, the classification module can receive more reliable information from the regression branch. When compared to the pioneering work 3D-CNN [6], our method outperforms it by a large margin, with 4.8%, 5.1%, and 1.6% performance improvement on accuracy, F1 score and AUC at image level. By and large, 3D-CNN has two drawbacks.…”
Section: Experiments and Resultsmentioning
confidence: 82%
“…Hence, several baseline methods, including an existing method as well as three variants of the proposed method, were implemented for comparison: (i). 3D-CNN: the implementation of the approach proposed in [6] which is trained with downsampled 3D volumes. (ii).…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Deep learning methods, such as convolutional neural networks (CNNs), directly operate on OCT volumes without any human-designed disease markers and can be considered feature-agnostic. 14,15 Most of the recent studies [15][16][17] have looked into optic nerve head OCT scans to detect glaucoma in well curated datasets, which exclude the challenging cases, such as glaucoma suspects, cases with high refractive error, or low signal strength. In this work, we include raw OCT macula scans from real-world scenarios for CNN training, and attempt to differentiate between high-risk cases, which require referral and evaluation by a glaucoma specialist and low-risk cases (split across referable vs. nonreferable disease) that can be observed without frequent testing.…”
Section: Introductionmentioning
confidence: 99%